Developing guidelines for good practice in the economic evaluation of occupational safety and health interventions - Emile Tompa; Jos Verbeek; Maurits van Tulder; Angela de Boer (Scandinavian Journal of Work, Environment & Health, 2010)

(untitled)
OBJECTIVES: One of the objectives of a recently held workshop in Amsterdam, the Netherlands, was to advance methods for the economic evaluation of occupational safety and health (OSH) interventions at the corporate and societal level. Drawing from that workshop, we discuss issues to consider when developing guidelines for good practice (ie, a reference case). METHODS: The Economics of Occupational Safety and Health (ECOSH) workshop was held in conjunction with the Repository of Occupational Well-being Economic Research (ROWER) initiative in the fall of 2009 and brought together researchers, employers, unions, policymakers, and other stakeholders. Through presentations, break-out sessions, and group discussions, efforts were made to develop a consensus on key elements for good practice. This manuscript integrates these efforts along with earlier contributions in this area. RESULTS: We propose some framework principles and a set of recommendations to serve as the foundations for developing a reference case. We argue that a reference case can be invaluable for the OSH field because it encourages sound principles to be consistently applied in studies. Furthermore, it can ensure that studies are more readily comparable regardless of the intervention type, jurisdiction, or sector. CONCLUSIONS: Developing guidelines for good practice in the economic evaluation of OSH interventions that meet the needs of all stakeholders requires discussion as well as time. The ECOSH/ROWER initiative has served as a good starting point for this objective.